Influence of quasicrystal I-phase on twinning of extruded Mg-Zn-Y alloys under compression. (1st June 2018) - Garces, G.; Medina, J.; Pérez, P.; Máthis, K.; Horváth, K.; Stark, A.; Schell, N.; Adeva, P.
Abstract: The interaction of the I-phase with twins during compression has been studied in a Mg-6Zn-1Y (wt.%) alloy using the combination of Synchrotron Radiation Diffraction and Acoustic Emission experiments during compression tests. The I-phase occurs as coarse particles at grain boundaries and nanosized precipitates within magnesium grains. Their interaction with twins depends on their shape and size. The presence of coarse I-phase particles with higher Young Modulus requires an additional stress for the activation of twinning since they induce tensile residual stresses in the magnesium matrix. Besides twinning, the basal and non-basal slip systems are also activated. Non-basal slip is observed after macroscopic yield stress within twins. The fine I-phase precipitates within grains interacts with the dislocations and the twins. In the latter case a back-stress arises, which acts against the compressive applied stress. This back stress hinders the twin growth more than the effect of the coarse particles. Graphical abstract: Image 1